(untitled) (Fiep Bulletin - online, 2011)
This study aims to understand the social relations involved in the sport in relations with leisure time working and not working while seeking to reflect the available time filled with sports and leisure practices can contribute to the achievement of well - physical and mental, with a view of human society and improving the quality of life for workers